What makes great data documentation? - Smith, Mark; Azimaee, Mahmoud (International Journal of Population Data Science, 2018)
Session topic: What makes great data documentation? Documentation is the tool that describes how and why a database was created, what its strengths and limitations are, and how all of the various components fit together. As such, it is an invaluable resource for helping others understand what they can do with the data. Please join us for a discussion of what makes great data documentation. This session will begin with a 40-minute integrated presentation by the Manitoba Centre for Health Policy (MCHP) and the Institute for Clinical Evaluative Sciences (ICES), two of the leading population data research centres in Canada, covering the following topics: 1 – Structured Overviews 2 – Data Models 3 – Data Dictionaries 4 – Other Documentation and Published Reports 5 – Integrating Blog or Analyst Notes 6 – Data Quality Reporting VIMO tables Heat maps Trend analysis Relevancy Session Facilitators: Mahmoud Azimaee, Institute for Clinical Evaluative Sciences (ICES) Mark Smith, Manitoba Centre for Health Policy (MCHP) The Intended Outcome: A research paper based on the discussion for publication in the International Journal of Population Data Science (IJPDS). All participants are invited to join us as co-authors in drafting and revising the paper.